Fertility options in transgender people. (2nd January 2016) - De Roo, Chloë; Tilleman, Kelly; T'Sjoen, Guy; De Sutter, Petra
Abstract: Hormonal and surgical treatments for transgender people have a devastating effect on the possibility for these patients to reproduce. Additionally, transgender people tend to start sex reassignment treatment at a young age, when reproductive wishes are not yet clearly defined nor fulfilled. The most recent Standards of Care of the World Professional Association for Transgender Health recommend clearly informing patients regarding their future reproductive options prior to initiation of treatment. This review gives an overview of the current knowledge and state-of-the-art techniques in the field of fertility preservation for transgender people. Where genital reconstructive surgery definitely results in sterility, hormone therapy on the other hand also has an important, but partially reversible impact on fertility. The current fertility preservation options for trans men are embryo cryopreservation, oocyte cryopreservation and ovarian tissue cryopreservation. For trans women, sperm cryopreservation, surgical sperm extraction and testicular tissue cryopreservation are possible. Although certain fertility preservation techniques could be applicable in a standardized manner based on clear biological criteria, the technique that eventually will be performed should be the preferred choice of the patient after extended explanation of all possible options.